Risk aversion for decisions under uncertainty: Are there gender differences? - Sarin, Rakesh; Wieland, Alice (Journal of Behavioral and Experimental Economics, 2016)
It has become well accepted that women are more risk averse than men. For objective probability gambles, typically used in eliciting risk aversion, we find women generally have a lower valuation than men, thus exhibiting greater risk aversion. This paper investigates whether this finding extends to decisions under uncertainty – where probabilities are not given and individuals may assign different probabilities to the same event (e.g. outcomes of award shows or sporting events).We find that for decisions under uncertainty, men and women value the bets similarly, both before and after controlling for participants' subjective probabilities.
Keywords: Decision-making; Gender; Risk aversion; Subjective probability; Uncertainty; dept.mgt; peer-reviewed

Boosting Performance on an Evaluative Math Test: Goal Activation vs Self-Affirmation - Wieland, Alice M.; Burnham, Thomas A. (Psychological Reports, 2016)
This study compared the effectiveness of goal activation versus self-affirmation and a control condition as interventions for increasing performance on an evaluative task (a difficult math test; N = 78; M age = 20.3 yr., SD = 1.9). Although there has been much recent literature on the effects of activating goals, the existing literature does not examine possible spillover effects of activating goals on performance tasks. Results indicated that goal activation resulted in significant performance enhancements over both the self-affirmation and control conditions, while self-affirmation did not improve performance significantly relative to the control condition. Additionally, interest in the task, as a cue for self-regulatory resources, mediated the effect of goal activation on increased performance.
Keywords: dept.mgt

Antecedents of corporate entrepreneurship in Iran: the role of strategic orientation and opportunity recognition - Kakapour, Saba; Morgan, Todd; Parsinejad, Salman; Wieland, Alice (Journal of Small Business & Entrepreneurship, 2016)
In a study of 130 Iranian small- and medium-sized enterprises (SMEs), we predict and find that market orientation, learning orientation, and their interaction are positively related to opportunity recognition, which impacts firm-level corporate entrepreneurship positively. This study makes two important contributions to the corporate entrepreneurship literature. First, the majority of studies on corporate entrepreneurship concern western economies or China; as such, we broaden research on the international context of corporate entrepreneurship by examining a unique dataset of Iranian SMEs, which have grown significantly in recent years during their transition to knowledge-based enterprises. Second, we build upon previous literature on corporate entrepreneurship antecedents by explicating and testing the relationships of how and when learning orientation and market orientation affect opportunity recognition and the development of corporate entrepreneurship.
Keywords: Apprentissage organisationnel; Entreprenariat d'entreprise; Entreprises fondées sur les connaissances; Iran; Orientation de marché; Orientation sur l'apprentissage; Petites et Moyennes Entreprises; Repérage des débouchés; corporate entrepreneurship; dept.mgt; knowledge-based enterprises; learning orientation; market orientation; opportunity recognition; organizational learning; peer-reviewed; small and medium-sized enterprises